Implementation of Agricultural Land Lease Agreements Based on Profit Sharing System in Kejajar District, Wonosobo Regency - Silvy Audia Rakhma; Susilo Wardani; Selamat Widodo (UMPurwokerto Law Review, 2021)
Most of the Wonosobo area is a mountainous area, therefore the livelihoods of the Wonosobo people are still mostly working in agriculture. In Kejajar District, Wonosobo Regency, farmers/cultivators usually enter into lease agreements with landowners. To use the agricultural land is done orally based on trust and has been passed down from generation to generation by the people of Kejajar District, Wonosobo Regency. This becomes unclear if there is a dispute between the landowner and the cultivator. So this research was conducted to find out how the process of implementing the lease of agricultural land. The research method used in this study is a normative juridical approach, which is carried out through a literature study that examines secondary data in the form of legislation and other legal documents, as well as research results, study results, and other references. The normative juridical method can be supplemented by interviews. The people of Kejajar District still use agricultural land production sharing agreements using customary law, which is only done verbally and based on mutual trust between the two parties, even though the government has provided a legal umbrella related to the agricultural land product sharing system, namely Law Number 2 of 1960 concerning Agricultural Product Sharing. Most of the people of the Kejajar Subdistrict, Wonosobo Regency are also not aware of the existence of Law Number 2 of 1960 concerning Agricultural Product Sharing. The factors that occur in the implementation of agricultural land production sharing agreements in Kejajar District, Wonosobo Regency are due to the large number of farmers who do not own land, agricultural land that has been neglected for a long time, landowners who do not have much time to take care of the land because they are busy trading.Keywords: Profit sharing, Agricultural land, Leases